PENINGKATAN HASIL BELAJAR IPAS PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN GOOGLE SITES DI KELAS VI SDN 03 IV KOTO AUR MALINTANG - Celsia Ditha Rahmani; Ahmad, Syafri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science learning outcomes of sixth-grade students at SDN 03 IV Koto Aur Malintang. The learning process was still conventional, lacked instructional media variation, and did not optimally involve students in active learning. This study aimed to describe the improvement of students’ science learning outcomes through the implementation of the Problem Based Learning (PBL) model assisted by Google Sites. The research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects were 18 sixth-grade students of SDN 03 IV Koto Aur Malintang in the first semester of the 2025/2026 academic year. Data were collected through observation, tests, and non-test techniques. The findings showed a significant improvement from Cycle I to Cycle II. The lesson plan assessment increased from 89.5% to 95.8%. Teacher activity improved from 87.4% to 100%, while student participation improved from good and sufficient categories to very good category. Students’ learning outcomes also increased from an average score of 71.7 in Cycle I to 95.6 in Cycle II. Therefore, the implementation of the Problem Based Learning (PBL) model assisted by Google Sites effectively improved students’ science learning outcomes.